2006
DOI: 10.1016/j.tics.2006.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Is neocortex essentially multisensory?

Abstract: Although sensory perception and neurobiology are traditionally investigated one modality at a time, real world behaviour and perception are driven by the integration of information from multiple sensory sources. Mounting evidence suggests that the neural underpinnings of multisensory integration extend into early sensory processing. This article examines the notion that neocortical operations are essentially multisensory. We first review what is known about multisensory processing in higher-order association c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

83
887
5
11

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,296 publications
(986 citation statements)
references
References 80 publications
83
887
5
11
Order By: Relevance
“…As mentioned earlier (see also other chapters in this issue), many human studies conducted with EEG or fMRI have revealed multisensory interactions in low-level cortices such as V1 (see Ghazanfar and Schroeder, 2006 for a review and Martuzzi et al, 2007;Romei et al, 2007Romei et al, , 2008 for recent evidences) and/or at a latency that strongly suggests that such phenomena are supported by the heteromodal connections directly linking areas of different sensory modalities. For example, the visual information derived from the lip movements during speech processing can affect directly the responses recorded in the auditory cortex (Besle et al, 2004).…”
Section: Electrophysiological Evidence In the Primary Sensory Areasmentioning
confidence: 81%
See 2 more Smart Citations
“…As mentioned earlier (see also other chapters in this issue), many human studies conducted with EEG or fMRI have revealed multisensory interactions in low-level cortices such as V1 (see Ghazanfar and Schroeder, 2006 for a review and Martuzzi et al, 2007;Romei et al, 2007Romei et al, , 2008 for recent evidences) and/or at a latency that strongly suggests that such phenomena are supported by the heteromodal connections directly linking areas of different sensory modalities. For example, the visual information derived from the lip movements during speech processing can affect directly the responses recorded in the auditory cortex (Besle et al, 2004).…”
Section: Electrophysiological Evidence In the Primary Sensory Areasmentioning
confidence: 81%
“…In this context, given the extensive connections between the neocortex, the superior colliculus and the thalamus, different authors have proposed that subcortical structures integrate the senses even before the neocortex (Ghazanfar and Schroeder, 2006 for review). The thalamus is a possible candidate considering its strong input-output connections with multiple cortical areas, both sensory and motor.…”
Section: Role Of the Thalamusmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, neurons responding to visual stimulation have been found in auditory cortex which may receive stimulation from higher areas or from subcortical regions via interconnections found in normal anatomy (Ghazanfar & Schroeder, 2006;Schroeder & Foxe, 2005). Such connections may function to improve spatial localisation of sound or amplify the auditory response to visually identifiable sources (Schroeder & Foxe, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…2009; Smeets and Dijksterhuis 2014). Olfactory sensory memory reflects activity, in part, within the primary olfactory cortex (POC), which like most sensory cortices (Ghazanfar and Schroeder 2006) receives direct and/or indirect convergent multisensory inputs (Gottfried et al. 2004; Wesson and Wilson 2010; Maier et al.…”
Section: Introductionmentioning
confidence: 99%